LPS-induced release of IL-6 from glia modulates production of IL-1? in a JAK2-dependent manner. - MINOGUE, AEDIN; BARRETT, JAMES; LYNCH, MARINA ANNETTA (My University, 2012)
Background: Compelling evidence has implicated neuroinflammation in the pathogenesis of a number of neurodegenerative conditions. Chronic activation of both astrocytes and microglia leads to excessive secretion of proinflammatory molecules such as TNF ? , IL-6 and IL-1 ? with potentially deleterious consequences for neuronal viability. Many signaling pathways involving the mitogen-activated protein kinases (MAPKs), nuclear factor ? B (NF ? B) complex and the Janus kinases (JAKs)/signal transducers and activators of transcription (STAT)-1 have been implicated in the secretion of proinflammatory cytokines from glia. We sought to identify signaling kinases responsible for cytokine production and to delineate the complex interactions which govern time-related responses to lipopolysaccharide (LPS). Methods: We examined the time-related changes in certain signaling events and the release of proinflammatory cytokines from LPS-stimulated co-cultures of astrocytes and microglia isolated from neonatal rats. Results: TNF ? was detected in the supernatant approximately 1 to 2 hours after LPS treatment while IL-1 ? and IL-6 were detected after 2 to 3 and 4 to 6 hours, respectively. Interestingly, activation of NF ? B signaling preceded release of all cytokines while phosphorylation of STAT1 was evident only after 2 hours, indicating that activation of JAK/STAT may be important in the up-regulation of IL-6 production. Additionally, incubation of glia with TNF ? induced both phosphorylation of JAK2 and STAT1 and the interaction of JAK2 with the TNF ? receptor (TNFR1). Co-treatment of glia with LPS and recombinant IL-6 protein attenuated the LPS-induced release of both TNF ? and IL-1 ? while potentiating the effect of LPS on suppressor of cytokine signaling (SOCS)3 expression and IL-10 release. Conclusions: These data indicate that TNF ? may regulate IL-6 production through activation of JAK/STAT signaling and that the subsequent production of IL-6 may impact on the release of TNF ? , IL-1 ? and IL-10
PUBLISHED
Keywords: Glia, Neuroinflammation, SOCS3, STAT1, TNFR1; Glia, Neuroinflammation, SOCS3, STAT1, TNFR1